The invisible hand of the government: “Moral suasion” during the European sovereign debt crisis - Steven Ongena; Alexander Popov; Neeltje Van Horen (European Central Bank (ECB), 2016)
Using proprietary data on banks' monthly securities holdings, we find that during the European sovereign debt crisis, domestic banks in fiscally stressed countries were considerably more likely than foreign banks to increase their holdings of domestic sovereign bonds in months with relatively high domestic sovereign bond issuance. This effect is stronger for state?owned banks and for banks with low initial holdings of domestic sovereign bonds, and it is not fuelled by Central Bank liquidity provision. Our results point to a “moral suasion” mechanism, and cannot be explained by concurrent risk?shifting, carry?trading, regulatory compliance, or shocks to investment opportunities.
Keywords: F34; G21; H63; 330; sovereign debt